Developmental counseling and therapy promoting wellness over the lifespan - Ivey, Allen (Lahaska Press, 2005)
Combining developmental counseling and therapy (DCT) theory with wellness theory and positive psychology, this text provides a foundation for addressing lifespan transitions and developmental issues. Students use case studies, transcripts, and exercises to learn how the major theories relate to actual practice.